Evaluation on Public Speaking Anxiety of Male and Female learners at Kampung Inggris Pare - Kadnawi (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2025)
Public speaking is an essential skill for English as a Foreign Language (EFL) learners, yet it often induces significant anxiety that hinders their academic, professional, and personal development. This study aims to evaluate the levels of public speaking anxiety among EFL learners and examine the relationship between state and trait anxiety using the State-Trait Anxiety Inventory (STAI). Employing a quantitative survey design, data were collected from 42 purposively selected EFL learners in Kampung Inggris, Pare, who participated in public speaking tasks such as presentations and discussions. Results revealed moderate to high levels of both state and trait anxiety, with female learners exhibiting slightly higher anxiety than males. The findings underscore the substantial role of trait anxiety in shaping learners’ speaking performance and highlight the need for targeted interventions, including anxiety management techniques, gender-sensitive support, and the creation of a safe learning environment. These implications are critical for developing effective strategies to reduce public speaking anxiety and enhance oral communication competence among EFL learners.